(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This thesis discusses the methodological possibilities of using tiered assignments in English language classes in higher education institutions. English language groups in higher education often have the characteristics of a mixed-ability classroom, where students differ in terms of language proficiency, grammatical competence, vocabulary knowledge, and written and oral communication skills. In such conditions, the use of tasks with the same level of complexity for all students may create difficulties for lower-level learners and limit developmental opportunities for higher-level learners. Tiered assignments, as one of the important strategies of differentiated instruction, make it possible to adapt tasks to students’ readiness levels and learning needs while maintaining a common learning objective.